GIL three-pillar grounding electrode copper / graphite system performance optimization method and system
Optimizing copper/graphite grounding electrode materials through plasma sintering technology and radar graph analysis method, solving the problem of insufficient wear resistance of grounding electrodes in GIL system, improving the overall performance of the material, and ensuring the safe and stable operation of the equipment.
Patent Information
- Application Number
- CN202411097046.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-01-03
AI Technical Summary
Inadequate wear resistance of ground electrodes in GIL systems leads to wear and insulation breakdown risks, affecting the safe and stable operation of the equipment.
The copper/graphite grounding electrode material is prepared by plasma sintering technology. By adjusting the graphite content and particle size, combining high-energy ball milling and plasma hot press sintering technology, the material performance is optimized, and a comprehensive performance evaluation is carried out through radar graph analysis.
It significantly improves the wear resistance, electrical conductivity and thermal conductivity of the grounding electrode, improves the density and overall performance of the material, solves the problems of uneven material performance and backward preparation process, and provides a better choice of grounding electrode materials.
Smart Images

Figure CN119252386A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of gas insulated transmission lines, and in particular relates to a method and system for optimizing the performance of a copper / graphite system of a GIL three-pillar grounding electrode. Background Art
[0002] In the GIL system, the grounding electrode at the end of the leg of the sliding three-pillar insulator is crucial to ensure stable contact between the insulator and the shell. However, during the long-term operation of the GIL, due to equipment vibration and thermal expansion and contraction of the shell, repeated friction will occur between the grounding electrode and the shell. This continuous friction will accelerate the material wear of the grounding electrode, especially for the copper electrode currently widely used. Wear not only leads to poor grounding of the three-pillar insulator, but also causes a large amount of metal chips to be generated, thereby increasing the risk of internal insulation breakdown and posing a threat to equipment safety. Therefore, the performance optimization of the grounding electrode is of great significance to the safe and stable operation of the GIL equipment.
[0003] Due to the poor wear resistance of pure copper, research on copper-based composite materials has been launched. Its excellent physical properties such as mechanical strength, dimensional stability, creep resistance, cyclic fatigue characteristics and excellent electrical and thermal properties are highly favored and widely used in many fields. Copper / graphite composite materials have both the high electrical and thermal conductivity of copper and the self-lubricating properties of graphite, and are mostly used in fields with special requirements for electrical conductivity and wear resistance.
[0004] Currently, there is an urgent need for a method to optimize the performance of the copper / graphite system of the GIL three-pillar grounding electrode. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a performance optimization method for a GIL three-pillar grounding electrode copper / graphite system based on plasma sintering technology, which aims to solve the problems of grounding electrode wear and insulation breakdown caused by insufficient wear resistance of existing grounding electrode materials and improve their wear resistance.
[0006] The present invention is implemented as follows: a method for optimizing the performance of a GIL three-pillar grounding electrode copper / graphite system, comprising the following steps:
[0007] Step 1, sintering to prepare optimized copper / graphite ground electrode material samples, wherein the ground electrode samples include samples with different graphite contents and different graphite particle sizes;
[0008] Step 2, testing various properties of the prepared ground electrode sample, including sample microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density;
[0009] Step 3, evaluate the performance of the grounding electrode material through radar chart analysis method, conduct comprehensive comparative analysis on the material's wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density, and obtain the grounding electrode material with the best comprehensive performance.
[0010] Furthermore, in step 1, a material sample of a copper / graphite grounding electrode is prepared by plasma hot pressing sintering technology.
[0011] Further, the method for preparing the material sample of the optimized copper / graphite ground electrode in step 1 comprises:
[0012] Step 1.1, pre-treating the raw materials of the grounding electrode, including alkali washing and acid washing;
[0013] Step 1.2, using a high-energy ball mill to fully mix the copper powder and the graphite powder, and setting the ball mill operating parameters, including speed, ball-to-material ratio, speed, and ball milling time;
[0014] Step 1.3, weighing the processed powder and loading it into the sintering mold;
[0015] Step 1.4, start sintering the sample and set the sintering parameters, including sintering temperature, sintering pressure, sintering time and vacuum degree in the furnace.
[0016] Furthermore, in step 2, the friction test machine parameters are set, including load, friction speed, friction stroke and friction time, and the wear resistance of the material is characterized by the friction coefficient and wear scar micrograph obtained by calculation and metallographic microscope:
[0017]
[0018] Among them, μ represents the friction coefficient, F is the friction force between objects, and N is the vertical force acting on the physical surface.
[0019] Furthermore, before the conductivity test in step 2, the tester needs to be calibrated to ensure the accuracy of the result.
[0020] Furthermore, in step 2, the Vickers hardness tester parameters are set, including the loading pressure and the holding time.
[0021] Further, in step 2, the parameters of the thermal conductivity tester are set and graphite is sprayed, and the parameters include the ambient temperature and the number of flash points.
[0022] Furthermore, in step 2, the density of the material is tested using the Archimedes drainage method:
[0023]
[0024] Among them, m is the physical weight, g is the gravitational acceleration, and V is the density of water and the volume of water displaced, respectively.
[0025] Furthermore, in step 3, the radar chart method is used to evaluate the comprehensive performance of the grounding electrode, and the benchmark value is selected to normalize the data and assign weights:
[0026]
[0027] Among them, θ represents the performance index obtained after normalization, X represents the original data, Y is the original data of pure copper, and ω represents the weight of the performance.
[0028] Another object of the present invention is to provide a GIL three-pillar grounding electrode copper / graphite system performance optimization method, comprising:
[0029] A material sample preparation module, for sintering and preparing material samples for optimizing copper / graphite grounding electrodes, wherein the grounding electrode samples include samples with different graphite contents and different graphite particle sizes;
[0030] The performance test module tests the various properties of the prepared ground electrode samples, including sample microstructure, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density;
[0031] The performance evaluation module evaluates the performance of grounding electrode materials through radar chart analysis, and conducts comprehensive comparative analysis on the wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density of the materials to obtain the grounding electrode material with the best comprehensive performance.
[0032] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0033] First, the method of the present invention prepares a copper / graphite grounding electrode composite material based on plasma sintering technology, improves the wear resistance of the grounding electrode by changing the graphite content and the graphite particle size, and tests the microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density of each material. Pure copper is selected as the reference value to normalize the tested values, and then weights are assigned according to the importance of each performance. The radar chart evaluation method is used to evaluate the comprehensive performance of each grounding electrode material, thereby achieving efficient and accurate performance optimization of the grounding electrode.
[0034] Second, the GIL three-pillar grounding electrode copper / graphite system performance optimization method proposed in the present invention comprehensively optimizes and evaluates the performance of the grounding electrode material through a series of detailed steps. The following is a detailed analysis of the parameters, algorithms and mathematical models of the present invention, as well as how they solve the existing technical problems and bring about technological progress:
[0035] Parameter setting and optimization
[0036] 1) Sintering preparation parameters:
[0037] Plasma hot pressing sintering technology is used, which can greatly shorten the sintering time and improve the density and performance of the material compared to traditional sintering methods.
[0038] The sintering parameters include sintering temperature, sintering pressure, sintering time and furnace vacuum, all of which are carefully adjusted to achieve the best sintering effect.
[0039] 2) Raw material processing parameters:
[0040] The raw materials are pre-treated by alkali washing and acid washing to remove impurities such as organic matter, inorganic salts and oxides on the surface to improve the purity of the material and the sintering quality.
[0041] The parameters of high-energy ball milling (rotation speed, ball-to-material ratio, and ball milling time) are precisely controlled to ensure that the copper powder and graphite powder can be fully mixed and to improve the interface bonding of the composite material.
[0042] 3) Performance test parameters:
[0043] The wear resistance test accurately characterizes the wear resistance of the material by setting parameters such as load, friction speed, friction stroke and friction time of the friction testing machine.
[0044] Calibrate the tester before the conductivity test to ensure the accuracy of the test results.
[0045] The parameters of the Vickers hardness tester and thermal conductivity tester are also precisely set to obtain reliable hardness and thermal conductivity data.
[0046] Algorithms and mathematical models
[0047] 1) Performance evaluation algorithm:
[0048] The radar chart analysis method is used to conduct a comprehensive comparative analysis of the wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density of the grounding electrode materials. This method can intuitively display the performance of the material in various performance indicators, making it easier to identify performance shortcomings and make targeted optimizations.
[0049] 2) Normalization and weight distribution:
[0050] In the radar chart analysis method, a benchmark value is selected to normalize the data to make the different performance indicators comparable.
[0051] According to the actual application requirements, weights are assigned to various performance indicators to more accurately reflect the comprehensive performance of the material in actual use.
[0052] Technical problems solved and technological progress
[0053] 1) Improve material performance:
[0054] Through precise parameter setting and optimization, the present invention can prepare a grounding electrode material with excellent wear resistance, high electrical conductivity, appropriate hardness and high thermal conductivity.
[0055] 2) Improve preparation efficiency:
[0056] The application of plasma hot pressing sintering technology has greatly shortened the sintering time, improved the preparation efficiency and reduced the production cost.
[0057] 3) Comprehensive performance evaluation:
[0058] The introduction of radar chart analysis provides an intuitive and comprehensive method for comprehensive performance evaluation of grounding electrode materials, which helps to guide the further optimization and practical application of materials.
[0059] In summary, the present invention effectively improves the comprehensive performance of the copper / graphite system of the GIL three-pillar grounding electrode through precise parameter setting, optimized preparation process and innovative performance evaluation method, and provides a better material choice for the grounding system in the power industry.
[0060] Third, the technical solution of the present invention solves the technical problems of the prior art.
[0061] 1) Uneven material properties: The copper / graphite grounding electrode materials in the prior art have uneven material properties at different graphite contents and particle sizes, making it difficult to achieve optimal comprehensive performance.
[0062] 2) Backward preparation process: Traditional preparation methods cannot fully utilize advanced manufacturing technologies, such as plasma hot pressing sintering technology, resulting in insufficient key properties such as material density, wear resistance and thermal conductivity.
[0063] 3) Incomplete performance evaluation: The existing technology lacks a systematic and scientific performance evaluation method, and it is impossible to comprehensively evaluate the material's wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, density and other properties.
[0064] 4) Insufficient energy consumption management: Issues such as the calibration of the conductivity tester, the setting of the friction tester parameters, and the ambient temperature control of the thermal conductivity tester were not considered, resulting in insufficient accuracy and consistency of the test results.
[0065] Significant technical advancements of the present invention:
[0066] 1) Optimize material preparation process:
[0067] The material density and overall performance of the copper / graphite ground electrode are improved through plasma hot pressing sintering technology. Plasma hot pressing sintering technology can sinter under high temperature and high pressure conditions, improving the mechanical and electrical properties of the material.
[0068] 2) Systematic performance testing and evaluation:
[0069] Comprehensive performance testing methods are provided, including tests on microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density, and specific test parameters are set. These tests ensure the accuracy and consistency of material performance.
[0070] 3) Comprehensive performance evaluation method:
[0071] The comprehensive performance of grounding electrode materials is evaluated by radar chart analysis, and wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density are comprehensively compared and analyzed. This method can systematically evaluate the comprehensive performance of materials and find the material with the best comprehensive performance.
[0072] 4) Efficient energy consumption management:
[0073] During the test, the accuracy and consistency of the test results were improved by setting the parameters of the friction tester, conductivity tester, Vickers hardness tester and thermal conductivity tester in detail and calibrating the conductivity tester.
[0074] The Archimedes drainage method is used to test the density of the material, and accurate density testing is ensured through precise measurement and calculation.
[0075] Specific examples of technological progress:
[0076] 1) Preparation process optimization:
[0077] The copper powder and graphite powder were fully mixed using high-energy ball milling, and the grounding electrode material was prepared by sintering using plasma hot pressing technology, which significantly improved the density and comprehensive performance of the material.
[0078] 2) Comprehensive performance test:
[0079] The prepared material samples are subjected to detailed tests on microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density, and specific test parameters and methods are provided to ensure the accuracy and repeatability of the test results.
[0080] 3) Radar chart analysis method:
[0081] The various properties of the materials are comprehensively evaluated through radar chart analysis, the data is normalized and weights are assigned to obtain the material with the best comprehensive performance.
[0082] The present invention significantly improves the comprehensive performance of the copper / graphite system of the GIL three-pillar grounding electrode by optimizing the material preparation process, systematic performance testing and evaluation methods, and efficient energy consumption management, solves the technical problems in the prior art, and achieves significant technical progress. These innovations and progress give the present invention significant advantages in material preparation, performance evaluation, and energy consumption management, and provide a solid technical foundation for the application of copper / graphite grounding electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 A schematic diagram of a ground electrode installation structure provided by an embodiment of the present invention;
[0084] Figure 2 Flow chart of the performance optimization method of the GIL three-pillar grounding electrode copper / graphite system provided by an embodiment of the present invention;
[0085] Figure 3 A sample diagram of a copper / graphite composite ground electrode material provided by an embodiment of the present invention;
[0086] Figure 4 Radar chart evaluation effect diagram provided by an embodiment of the present invention; (a) graphite particle size 4 μm, (b) graphite particle size 40 μm;
[0087] Figure 5 A structural diagram of a GIL three-pillar grounding electrode copper / graphite system performance optimization system provided in an embodiment of the present invention.
[0088] Figure 6 Friction coefficient variation diagram of the ground electrode sample provided in the embodiment of the present invention; (a) graphite particle size 4 μm, (b) graphite particle size 40 μm;
[0089] Figure 7 The electrical conductivity of each sample of the ground electrode provided by the embodiment of the present invention;
[0090] Figure 8 Vickers hardness of each sample of the ground electrode provided by the embodiment of the present invention;
[0091] Fig. 9 Thermal conductivity of each ground electrode sample provided by the embodiment of the present invention;
[0092] Fig.10 The density of each ground electrode sample provided by the embodiment of the present invention; DETAILED DESCRIPTION
[0093] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0094] See also Figure 2 The embodiment of the present invention provides a method for optimizing the performance of a GIL three-pillar ground electrode copper / graphite system based on plasma sintering technology, comprising the following steps:
[0095] Step 1, sintering to prepare optimized copper / graphite ground electrode material samples, wherein the ground electrode samples include samples with different graphite contents and different graphite particle sizes;
[0096] Step 2, testing various properties of the prepared ground electrode sample, including sample microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density;
[0097] Step 3, evaluate the performance of the grounding electrode material through radar chart analysis method, conduct comprehensive comparative analysis on the material's wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density, and obtain the grounding electrode material with the best comprehensive performance.
[0098] Furthermore, in step 1, a material sample of a copper / graphite grounding electrode is prepared by plasma hot pressing sintering technology.
[0099] Further, the method for preparing the material sample of the optimized copper / graphite ground electrode in step 1 comprises:
[0100] Step 1.1, pre-treating the raw materials of the grounding electrode, including alkali washing and acid washing;
[0101] Step 1.2, using a high-energy ball mill to fully mix the copper powder and the graphite powder, and setting the ball mill operating parameters, including speed, ball-to-material ratio, speed, and ball milling time;
[0102] Step 1.3, weighing the processed powder and loading it into the sintering mold;
[0103] Step 1.4, start sintering the sample and set the sintering parameters, including sintering temperature, sintering pressure, sintering time and vacuum degree in the furnace.
[0104] Further, in step 2, the friction test machine parameters are set, including load, friction speed, friction stroke and friction time, and the wear resistance of the material is characterized by the friction coefficient and wear scar micrograph obtained by calculation and metallographic microscope:
[0105]
[0106] Among them, μ represents the friction coefficient, F is the friction force between objects, and N is the vertical force acting on the physical surface.
[0107] Furthermore, in step 2, the tester needs to be calibrated before the conductivity test to ensure the accuracy of the result.
[0108] Further, in step 2, the Vickers hardness tester parameters are set, including loading pressure and holding time.
[0109] Further, in step 2, the parameters of the thermal conductivity tester are set and graphite is sprayed, the parameters including the ambient temperature and the number of flash points.
[0110] Furthermore, in step 2, the density of the material is tested using the Archimedes drainage method:
[0111]
[0112] Among them, m is the physical weight, g is the gravitational acceleration, and V is the density of water and the volume of water displaced, respectively.
[0113] Furthermore, in step 3, the radar chart method is used to evaluate the comprehensive performance of the grounding electrode, the benchmark value is selected to normalize the data, and the weight is assigned:
[0114]
[0115] Among them, θ represents the performance index obtained after normalization, X represents the original data, Y is the original data of pure copper, and ω represents the weight of the performance.
[0116] The present invention utilizes plasma sintering technology to prepare copper / graphite composite grounding electrode materials with different graphite contents and graphite particle sizes, and optimizes the performance of the grounding electrode material by testing and analyzing the microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density of the grounding electrode material, and using radar charts to evaluate the comprehensive performance of the material.
[0117] Grounding electrode installation structure Figure 1 As shown, the copper / graphite composite grounding electrode material sample is as follows Figure 2 shown.
[0118] See also Figure 2 The embodiment of the present invention provides a method for optimizing the performance of a GIL three-pillar ground electrode copper / graphite system based on plasma sintering technology, comprising the following steps:
[0119] Step 101, sintering to prepare copper / graphite grounding electrode composite material samples, the grounding electrode samples include samples with different graphite contents and different graphite particle sizes, wherein the sample design mass is 10g, the graphite contents are 3%, 5%, 7%, and 10%, respectively, and the graphite particle sizes are 4μm and 40μm, respectively; material pretreatment, using 60g / L NaOH solution for alkaline washing and 200g / L HNO3 solution for acid washing; during the ball milling process, the ball-to-material ratio is set to 10:1, and the ratio of large, medium and small balls is followed to be 5:3:1. At a rotation speed of 900r / min, ball milling lasts for 20min; sintering includes five stages, the first three stages are the heating process, the temperature gradually rises from 700℃ to 960℃, and the pressure is reduced to 20MPa in the third stage; the fourth stage is the insulation stage, keeping the parameters in the furnace stable for 10min; the last stage is cooling, reducing the temperature in the furnace to 0; sampling is performed after the temperature and pressure in the furnace drop to 0, and the obtained copper-based composite material is finely ground and polished.
[0120] Table 1 Material composition ratio
[0121] Grounding electrode material Cu(g) Graphite(g) Cu-C3% 9.7 0.3 Cu-C5% 9.5 0.5 Cu-C7% 9.3 0.7 Cu-C10% 9.0 1.0
[0122] Table 2 Sintering parameters
[0123]
[0124] Step 102, testing various properties of the prepared grounding electrode sample, the specific properties include sample microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density; the microstructure morphology is analyzed by SEM and EDS, the wear resistance is tested by a 339-GSRⅡ steel wool friction tester, and a 20-minute ball-disc friction test is performed under a load of 25g. The electrical conductivity is measured by a D60K digital metal conductivity meter to measure the electrical conductivity of the copper-based grounding electrode material, and the electrical conductivity data of the grounding electrode is directly obtained by a metal probe. The Vickers hardness is measured according to the method in the standard GB / T7997-2014, and the hardness test of the copper / graphite composite material is carried out by using a HVS-1000Z Vickers hardness tester. During the test, the applied pressure is set to 500N and the application time is 5s. The thermal conductivity is measured by LFA The 447 thermal conductivity tester measures the thermal conductivity of copper / graphite composite samples. To ensure the accuracy and stability of the test, a layer of graphite film needs to be sprayed on the clean and smooth material surface to improve the measurement accuracy of the thermal conductivity. The density is measured by the Archimedes drainage method in conjunction with the ET-320 electronic density meter to measure the buoyancy of the object when it is completely immersed in the liquid, and then the density of the object is accurately calculated through the relationship between the buoyancy and the mass and volume of the object.
[0125] Step 103, evaluate the performance of the grounding electrode material by radar chart analysis, conduct comprehensive comparative analysis on the wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density of the material, and obtain the grounding electrode material with the best comprehensive performance; determine the weight distribution of the GIL grounding electrode performance index as follows: wear resistance accounts for 50%, Vickers hardness accounts for 15%, electrical conductivity accounts for 15%, density and thermal conductivity each account for 10%. Since the grounding electrode in GIL generally uses pure copper material, the present invention uses the performance of pure copper as a benchmark, and normalizes the data by the following formula to ensure the accuracy and objectivity of the evaluation results.
[0126]
[0127] Among them, θ represents the performance index obtained after normalization, X represents the original data, and Y represents the original data of pure copper. ω represents the weight of the performance.
[0128] Grounding electrode performance optimization effect Figure 4 shown.
[0129] like Figure 5 The embodiment of the present invention provides a GIL three-pillar grounding electrode copper / graphite system performance optimization method, comprising:
[0130] A material sample preparation module, for sintering and preparing material samples of optimized copper / graphite grounding electrodes, wherein the grounding electrode samples include samples with different graphite contents and different graphite particle sizes;
[0131] The performance test module tests the various properties of the prepared ground electrode samples, including sample microstructure, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density;
[0132] The performance evaluation module evaluates the performance of grounding electrode materials through radar chart analysis, and conducts comprehensive comparative analysis on the wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density of the materials to obtain the grounding electrode material with the best comprehensive performance.
[0133] Example 1
[0134] Step 1: Sintering to prepare the material sample for the optimized copper / graphite ground electrode
[0135] 1) Raw material pretreatment
[0136] The copper powder and graphite powder are alkali washed and acid washed to remove surface impurities and oxides.
[0137] 2) High energy ball milling
[0138] Use a high-energy ball mill to mix the pretreated copper powder and graphite powder. Set the ball mill parameters as follows: speed 400 rpm, ball-to-material ratio 10:1, and ball milling time 4 hours.
[0139] 3) Weighing and loading into sintering mold
[0140] The well-mixed copper / graphite powder was weighed and loaded into the sintering mold, ensuring uniform filling.
[0141] 4) Plasma hot pressing sintering
[0142] The plasma hot pressing sintering technology is used for sintering, and the sintering temperature is set to 900°C, the sintering pressure is 30MPa, the sintering time is 2 hours, and the vacuum degree in the furnace is 10^-3Pa.
[0143] Step 2: Test the properties of the prepared ground electrode samples
[0144] 1) Microstructure morphology
[0145] Scanning electron microscopy (SEM) was used to observe the microstructure morphology of the samples.
[0146] 2) Wear resistance
[0147] The friction tester parameters were set as follows: load 5N, friction speed 0.1m / s, friction stroke 10mm, and friction time 30min. The friction coefficient was calculated and the wear marks were observed with a metallographic microscope.
[0148] 3) Conductivity
[0149] After calibrating the conductivity tester, measure the conductivity of the sample.
[0150] 4) Vickers hardness
[0151] Set the Vickers hardness tester parameters: loading pressure 10N, holding time 15 seconds, and measure the Vickers hardness of the sample.
[0152] 5) Thermal conductivity
[0153] Set the thermal conductivity tester parameters: ambient temperature 25°C, flash point number 5 times, and measure the thermal conductivity of the sample after graphite spraying.
[0154] 6) Density
[0155] The density of the samples was measured using the Archimedean displacement method.
[0156] Step 3: Evaluate ground electrode material performance using radar chart analysis
[0157] 1) Data normalization
[0158] The reference values were selected to normalize the data of wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density.
[0159] 2) Assign weights
[0160] Assign weights to each performance and calculate comprehensive performance indicators.
[0161] 3) Draw a radar chart
[0162] The normalized data are plotted into a radar chart, and comprehensive comparative analysis is performed to obtain the grounding electrode material with the best comprehensive performance.
[0163] Example 2
[0164] Step 1: Sintering to prepare the material sample for the optimized copper / graphite ground electrode
[0165] 1) Raw material pretreatment
[0166] The copper powder and graphite powder are alkali washed and acid washed to remove surface impurities and oxides.
[0167] 2) High energy ball milling
[0168] Use a high-energy ball mill to mix the pretreated copper powder and graphite powder. Set the ball mill parameters as follows: speed 500 rpm, ball-to-material ratio 12:1, and ball milling time 3 hours.
[0169] 3) Weighing and loading into sintering mold
[0170] The well-mixed copper / graphite powder was weighed and loaded into the sintering mold, ensuring uniform filling.
[0171] 4) Plasma hot pressing sintering
[0172] The plasma hot pressing sintering technology is used for sintering, and the sintering temperature is set to 950°C, the sintering pressure is 35MPa, the sintering time is 1.5 hours, and the vacuum degree in the furnace is 10^-4Pa.
[0173] Step 2: Test the properties of the prepared ground electrode samples
[0174] 1) Microstructure morphology
[0175] Scanning electron microscopy (SEM) was used to observe the microstructure morphology of the samples.
[0176] 2) Wear resistance
[0177] The friction tester parameters were set as follows: load 7N, friction speed 0.2m / s, friction stroke 8mm, and friction time 25min. The friction coefficient was calculated and the wear marks were observed using a metallographic microscope.
[0178] 3) Conductivity
[0179] After calibrating the conductivity tester, measure the conductivity of the sample.
[0180] 4) Vickers hardness
[0181] Set the Vickers hardness tester parameters: loading pressure 20N, holding time 10 seconds, and measure the Vickers hardness of the sample.
[0182] 5) Thermal conductivity
[0183] Set the thermal conductivity tester parameters: ambient temperature 20°C, flash point count 3 times, and measure the thermal conductivity of the sample after graphite spraying.
[0184] 6) Density
[0185] The density of the samples was measured using the Archimedean displacement method.
[0186] Comprehensive performance evaluation:
[0187] Step 3: Evaluate ground electrode material performance using radar chart analysis
[0188] 1) Data normalization
[0189] The reference values were selected to normalize the data of wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density.
[0190] 2) Assign weights
[0191] Assign weights to each performance and calculate comprehensive performance indicators.
[0192] 3) Draw a radar chart
[0193] The normalized data are plotted into a radar chart, and comprehensive comparative analysis is performed to obtain the grounding electrode material with the best comprehensive performance.
[0194] The technical effects obtained by the embodiments of the present invention are as follows:
[0195] 1. Wear resistance: see attached Figure 6The friction coefficient change diagram of the grounding electrode material shows that when the graphite particle size is 4μm, the friction coefficient curves of 3%, 5%, 7% and 10% copper / graphite composite materials all show a trend of first increasing and then stabilizing. The friction coefficient of copper graphite with a graphite content of 3% and 7% is stable at around 0.75, and the copper graphite with a graphite content of 5% is stable at around 0.85, while the friction coefficient of the material with a graphite content of 10% is stable at around 0.9. When the graphite particle size is 40μm, the friction coefficient curves of copper graphite with a graphite content of 5%, 7% and 10% all show a trend of first rising and then falling and tending to stabilize, which is similar to the phenomenon when the particle size is 4μm. After the wear stabilizes, the friction coefficient stabilizes in the range of 0.7-0.8. The friction coefficient of the copper graphite sample with a graphite content of 3% is higher, stable between 0.8-0.9, and the friction coefficient of the copper graphite sample with a graphite content of 7% is stable in the range of 0.7-0.8 due to the increase in graphite content.
[0196] 2. Conductivity: see attached Figure 7 The conductivity diagram of each grounding electrode sample shows that as the graphite content increases, the conductivity of the copper-graphite composite material continues to decrease. When the graphite particle size is 4μm, the conductivity drops to the lowest at a graphite mass fraction of 10%, about 18.9MS / m. When the graphite particle size is 40μm, it is still the lowest when the graphite mass fraction is 10%, dropping to 17.5MS / m. The overall conductivity of the copper-graphite grounding electrode material with a graphite particle size of 40μm is low, which is because the increase in the graphite particle size increases the probability of contact between copper particles and graphite particles.
[0197] 3. Hardness: see attached Figure 8 Vickers hardness diagram of ground electrode samples. It can be seen from the figure that the hardness of the sample decreases with the increase of graphite mass fraction, and the hardness is about 50.1HV when the graphite mass fraction is 10%. The graphite particle size of 40μm is consistent with the graphite particle size of 4μm. The hardness of the sample decreases with the increase of graphite mass fraction, but its overall hardness is less than the hardness of the particle size of 4μm. When the graphite mass fraction is 10%, its hardness is only 22.3HV.
[0198] 4. Thermal conductivity: see attached Fig. 9 The thermal conductivity diagram of each ground electrode sample shows that compared with the graphite particle size of 40μm, the graphite particle size of 4μm shows higher thermal conductivity in the copper / graphite composite material. This is attributed to the fact that the small-particle graphite significantly increases the contact probability between copper and graphite particles, thereby optimizing the heat conduction efficiency in the composite material. In addition, the small-particle graphite also enhances the density of the composite material, further reducing heat loss. However, with the increase of graphite mass fraction, the thermal conductivity of the composite material shows a downward trend. This is because although the high-content graphite particles form more heat conduction paths, the low thermal conductivity of graphite in the direction perpendicular to the crystal, coupled with the accumulation of thermal resistance between the copper and graphite interfaces, jointly affects the improvement of thermal conductivity.
[0199] 5. Density: see attached Fig.10 Density diagram of ground electrode samples. The density of pure copper is 8.89g / cm 3 , while the density of graphite is lower, which is 2.26g / cm 3 Therefore, as the graphite content increases, the density of the composite material gradually decreases. Specifically, when the mass fraction of graphite is 3%, 5%, 7% and 10%, the theoretical density of the composite material is 8.22 g / cm 3 , 7.798g / cm 3 , 7.511g / cm 3 and 6.823g / cm 3 This is basically consistent with the experimental results.
[0200] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for optimizing the performance of a GIL three-pillar grounding electrode copper / graphite system, characterized in that: The following steps are involved: Step 1, sintering to prepare optimized copper / graphite ground electrode material samples, wherein the ground electrode samples include samples with different graphite contents and different graphite particle sizes; Step 2, testing various properties of the prepared ground electrode sample, including sample microstructure morphology, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density; Step 3, evaluate the performance of the grounding electrode material through radar chart analysis method, conduct comprehensive comparative analysis on the material's wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density, and obtain the grounding electrode material with the best comprehensive performance.
2. The GIL three-pillar grounding electrode copper / graphite system performance optimization method according to claim 1, characterized in that: In step 1, a material sample of a copper / graphite ground electrode is prepared by plasma hot pressing sintering technology.
3. The GIL three-pillar grounding electrode copper / graphite system performance optimization method according to claim 1, characterized in that: The method for preparing the material sample of the optimized copper / graphite ground electrode in step 1 comprises: Step 1.1, pre-treating the raw materials of the grounding electrode, including alkali washing and acid washing; Step 1.2, using a high-energy ball mill to fully mix the copper powder and the graphite powder, and setting the ball mill operating parameters, including speed, ball-to-material ratio, speed, and ball milling time; Step 1.3, weighing the processed powder and loading it into the sintering mold; Step 1.4, start sintering the sample and set the sintering parameters, including sintering temperature, sintering pressure, sintering time and vacuum degree in the furnace.
4. The method for optimizing the performance of the GIL three-pillar grounding electrode copper / graphite system according to claim 1, characterized in that: In step 2, set the friction test machine parameters, including load, friction speed, friction stroke and friction time, and characterize the wear resistance of the material through calculation and the friction coefficient and wear scar micrograph obtained by metallographic microscope: Among them, μ represents the friction coefficient, F is the friction force between objects, and N is the vertical force acting on the physical surface.
5. The GIL three-pillar grounding electrode copper / graphite system performance optimization method according to claim 1, characterized in that: Before the conductivity test in step 2, the tester needs to be calibrated to ensure the accuracy of the result.
6. The GIL three-pillar grounding electrode copper / graphite system performance optimization method according to claim 1, characterized in that: In step 2, set the Vickers hardness tester parameters, including loading pressure and holding time.
7. The method for optimizing the performance of the GIL three-pillar grounding electrode copper / graphite system according to claim 1, characterized in that: In step 2, set the parameters of the thermal conductivity tester and spray graphite, including the ambient temperature and the number of flash points.
8. The method for optimizing the performance of the GIL three-pillar grounding electrode copper / graphite system according to claim 1, characterized in that: In step 2, the density of the material is tested using the Archimedes drainage method: Among them, m is the physical weight, g is the gravitational acceleration, and V is the density of water and the volume of water displaced, respectively.
9. The method for optimizing the performance of the GIL three-pillar grounding electrode copper / graphite system according to claim 1, characterized in that: In step 3, the radar chart method is used to evaluate the comprehensive performance of the grounding electrode, and the benchmark value is selected to normalize the data and assign weights: Among them, θ represents the performance index obtained after normalization, X represents the original data, Y is the original data of pure copper, and ω represents the weight of the performance.
10. A GIL three-pillar grounding electrode copper / graphite system performance optimization method according to any one of claims 1 to 9, characterized in that: include: A material sample preparation module, for sintering and preparing material samples for optimizing copper / graphite grounding electrodes, wherein the grounding electrode samples include samples with different graphite contents and different graphite particle sizes; The performance test module tests the various properties of the prepared ground electrode samples, including sample microstructure, wear resistance, electrical conductivity, Vickers hardness, thermal conductivity, and density; The performance evaluation module evaluates the performance of grounding electrode materials through radar chart analysis, and conducts comprehensive comparative analysis on the wear resistance, electrical conductivity, Vickers hardness, thermal conductivity and density of the materials to obtain the grounding electrode material with the best comprehensive performance.
Citation Information
Cited By
Multi-feature and integrated optimization saline-alkali soil conductivity prediction method
CN120524463A
A multi-feature and integrated optimization method for predicting soil salinity conductivity
CN120524463B